The Malaysian Land Taxation System: A Chronological Review Of The Torrens System From The Islamic Perspective - Fuadah Johari; Patmawati Ibrahim; Wirdati Mohd. Radzi; Mohd.Firdaus Ibrahim (Landesmuseum Karnten, 2024)
Vol 21, No. 1;Jan 2014